Opinion Mining from Customer Reviews for Product Ranking - Jahiruddin, Jahiruddin (International Journal of Computer Sciences and Engineering, 2025)
Recently the peoples of the metropolitan cities are moving from traditional offline interactive shopping to online shopping due to time limitation and cost of products. In online shopping, the purchase decision is a challenging task for new customers as there may a large number of competitive products. Recently mostly online shopping sites have been facilitated to their customers to write the reviews about the products they have purchased. These customers’ reviews do not only help to new customer for taking purchase decision but also help the manufacturer to increase the sale of their products by improving its quality. This paper presents a reviews mining method to extract product features and its opinion. Thereafter, we apply the Analytic Hierarchy Process (AHP) on extracted features and opinion to rank the competitive products by scoring them. The method has been validated on a data set related to five smart phones downloaded from three deferent online shopping websites - Flipkart, Snapdeal, and Amazon. The evaluation result shows that the proposed method gives up to marks result.